2019
DOI: 10.3390/jcm8101593
|View full text |Cite
|
Sign up to set email alerts
|

The White Blood Cell Count to Mean Platelet Volume Ratio for the Prediction of Chronic Limb-Threatening Ischemia in Lower Extremity Artery Disease

Abstract: : Background: The white blood cell count to mean platelet volume ratio (WMR) is increasingly gaining importance as a promising prognostic marker in atherosclerotic disease, but data on lower extremity artery disease (LEAD) are not yet available. The principle aim of this study was to assess the association of the WMR with the occurrence of CLTI (chronic limb-threatening ischemia) as the most advanced stage of disease. Methods: This study was performed as a retrospective analysis on 2121 patients with a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Plateletmediated infl ammation has been reported to contribute to cancer progression with platelet-derived growth factors contributing to oncogenic transformation and tumorigenesis [26]. The risk models for predicting survival and/or progression of disorders include NLR and PLR values based on the role of WBCs and platelets in the initiation, progression, and complications of cardiovascular-related diseases [27] were reported to increase in this study. Higher NLR and PLR detect infl ammatory activation underlying some disorders such as cardiovascular disorders, cancers, etc.…”
Section: Discussionmentioning
confidence: 62%
“…Plateletmediated infl ammation has been reported to contribute to cancer progression with platelet-derived growth factors contributing to oncogenic transformation and tumorigenesis [26]. The risk models for predicting survival and/or progression of disorders include NLR and PLR values based on the role of WBCs and platelets in the initiation, progression, and complications of cardiovascular-related diseases [27] were reported to increase in this study. Higher NLR and PLR detect infl ammatory activation underlying some disorders such as cardiovascular disorders, cancers, etc.…”
Section: Discussionmentioning
confidence: 62%
“…CLTI is a clinical syndrome expressing the most advanced stages of PAD and is associated with amputation, impaired quality of life, and mortality. 16,17 In a meta-analysis that consisted of 13 studies with untreated CLTI patients (1527 patients), the rate of wound ulcers was reported to be 35%, major amputation rate was 22%, and mortality rate was 22% in a median one-year follow-up. 18 The main cause is atherosclerosis in CLTI pathology, and although many predictors have been identified in recent years for the detection of PAD patients who are at risk of CLTI development, this issue continues to be popular because of poor prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to medical treatments (antithrombotic, lipid-lowering, antihypertensive agents) and treatment approaches such as exercise, diet, smoking cessation, and preventive foot care applied in symptomatic LEAD patients, early revascularization options are recommended for patients at high risk of developing CLTI [1,3]. In recent years, many predictors of CLTI development have been identified in patients diagnosed with LEAD [16,17]. Since atherosclerosis is the underlying cause of LEAD pathology, the identified predictors are focused on atherosclerosis, which is considered an inflammatory process.…”
Section: The Relation Between Clti Development and Calculated Po Values And Aip Values Was Investigated Inmentioning
confidence: 99%